An Investigation of 8th Grade Students’ Knowledge about Linear Equations - Bi̇ber, Abdullah Çağrı (Cumhuriyet International Journal of Education, 2014)
The purpose of this study was to determine mistakes and misconceptions, if there are any, of the 8th grade students regarding “linear equations”. Among the participants of the study were 23 eight grade students from a secondary school located in the North part of Turkey. The study was applied during the second half of 2012-2013 academic years. In the research, four open-ended questions were utilized to achieve the intended goal. According to the results of the study, students have some mistakes and misconceptions regarding determining the points in which the line crosscuts the axis, can not associate linear equation with slope, can not draw the graph of a line the equation of which is given, can not find the equation of a line the graph of which is given, have missing information about the condition of being parallel to the axis and do not conceive the situation completely.
Keywords: Misconceptions; Linear equation; Linear equation; isconceptions; middle school mathematics educations; 13. Climate action; 4. Education